Blood Donation Motivation In Building Blood Donor Perception (Self Determination Theory Perspective) - Yuliatin Azizah; Tamriatin Hidayah; Saiful Amin (ABM: International Journal of Administration, Business and Management, 2024)
The availability of blood is highly dependent on donors. The phenomenon of the perception of blood as expensive or sold is also often heard, which means that distrust of blood donors affects the motivation to donate. Increasing perception with donor motivation as volunteers to be willing to help patients in need. For this reason, we are interested in research on the influence of self-determination theory on donor perceptions. The research method used is quantitative SEM PLS with the help of the Wrap PLS 7.0 calculation tool. The research sample used the V region of East Java, Indonesia because this area is most often hit by natural disasters so the blood donor is needed. All question items have been valid and reliable with the results of the study explaining the very good model of Amotivation, External Regulation, Introjected Regulation has no effect on perception. Identification regulation, integration regulation, intrinsic regulation can be used to build blood donor perceptions.